MODULAR EXPONENTIATION - Iftene, Sorin (International Journal of Computing, 2014)
Exponentiation is a fundamental operation in computational number theory. Primality testing and cryptography are important working fields in which the exponentiation is heavily used. In this paper we survey the most popular methods for modular exponentiation: basic techniques, fixed-exponent techniques, fixed-base techniques, and techniques based on modulus particularities. Some aspects related to parallelism are also discussed.